PENGARUH SANKSI, MOTIVASI DAN TINGKAT PENDIDIKAN TERHADAP KEPATUHAN WAJIB PAJAK ORANG PRIBADI (STUDI KASUS KPP PRATAMA MANADO) - Tologana, Evalin Yuanita (ACCOUNTABILITY, 2015)
This study aim to determine the effect of sanctions, motivation and level of education on tax compliance. Population in this study is the taxpayer listed in KPP Pratama Manado. Samples used were 100 taxpayer who are determine using a formula slovin. Data were analyzed using multiple linear regression followed by normality test, multicolinearity test, heterocedasticity test and autocorrelation test. The result showed the tax motivation sanctions and positive effect on tax compliance while education level had no effect on tax compliance.